Does Profitability Undermine Social Accountability? Evidence From Indonesian Islamic Banking - Deby Liyana Putri Utami; Romi Adetio Setiawan; Risky Hariyadi; Ledya Febrianti; Muhammadtolan Kaemah (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
This study analyses the influence of company size and profitability on Islamic Social Reporting (ISR) disclosure in Islamic Banks in Indonesia for the 2019-2023 period. Secondary data were collected from the annual reports of eight banks with a total of 40 observations. Company size was measured using the natural logarithm of total assets, profitability was measured by Return on Assets (ROA), and ISR was measured based on an index of 43 indicators across six disclosure themes. The results of multiple linear regression analysis show that company size has no significant effect on ISR, while profitability has a significant negative effect. Simultaneously, both variables significantly influence ISR, although they only explain 13.6% of the disclosure variation (Adj R² = 0.136). These findings indicate that ISR disclosure in Indonesian Islamic banking is not fully driven by economic factors but is more influenced by sharia commitment and other non-financial factors. Consequently, Islamic banks need to strengthen their social accountability as a manifestation of sharia integrity, not merely as a response to financial performance.